Integrity as a Moderator of the Influence of the Internal Control System on Accounting Fraud - PUTRA, I Gst. B. Ngr. P.; MAHARANI, Ida Ayu Dinda Priyanka (PT Keberlanjutan Strategis Indonesia, 2024)
Organizations in the financial sector, like the Village Credit Institution (LPD) in Bali, are highly prone to accounting fraud. Despite their importance, fraudulent actions by LPD managers are still common. To reduce fraud, an effective internal control system is essential. Motivated by inconsistent results in previous studies, this research introduces individual integrity as a moderating variable. The study focuses on LPDs in Badung Regency, using purposive sampling to select participants based on specific criteria. The criteria used as the basis for selecting sample members in this study were LPDs with healthy and fairly healthy categories, totaling 71 LPDs. Meanwhile, the respondents to the study in each LPD were the Head of LPD, LPD Treasurer and Credit Division, while the number of respondents was 213 research respondents. The data analysis technique in this study uses the structural equation modeling (SEM) method based on partial least square (PLS). The statistical test results obtained the results that the internal control system variable has a significant negative effect on the tendency of accounting fraud. While the individual integrity level variable strengthens the influence of the internal control system on the tendency of accounting fraud.